Dark matter searches in CMS. (May 2015) - Daci, Nadir
Abstract: The CMS collaboration searched for Dark Matter (DM) particles produced in pairs in proton-proton (pp) collisions performed by the LHC at a centre-of-mass energy of 8 TeV, corresponding to an integrated luminosity of 19.7 /fb. The following signatures were investigated: a single boosted object and a significant transverse momentum imbalance; associated production of DM with a pair of top quarks; decay of a Higgs boson (H) into a pair of DM particles. Exclusion limits were set on the cross sections of DM production and interaction cross sections, as a function of the DM particle mass.